Tetraploid embryo aggregation produces high-quality blastocysts with an increased trophectoderm in pigs - Lee, Joohyeong; Cai, Lian; Kim, Mirae; Choi, Hyerin; Oh, Dongjin; Jawad, Ali; Lee, Eunsong; Hyun, Sang-Hwan (Frontiers in Cell and Developmental Biology, 2023)
Tetraploid complementation is an ideal method for demonstrating the differentiation potential of pluripotent stem cells. In this study, we selected the most efficient tetraploid production method for porcine embryos and investigated whether tetraploid blastomere aggregation could enhance the quality of tetraploid embryos. Three methods were investigated to produce tetraploid embryos: First, tetraploid embryos were produced using electro-fusion of two-cell stage parthenogenetic blastomere (FUTP). Second, somatic cell was injected into the mature oocyte and fused to produce tetraploid embryos. Third, oocytes were matured with Cytochalasin B (CB) for the late 22 h of in vitro maturation to inhibit the first polar body (PB1). Following that, non-PB1 oocytes were treated with CB for 4 h after parthenogenetic activation. There was no significant difference in the blastocyst development rate and tetraploid production rate of the embryos produced through the three methods. However, FUTP-derived blastocysts had a significantly lower percentage of apoptotic cells compared to other methods. The developmental competence of embryos, expression of trophectoderm cell This is a provisional file, not the final typeset article marker genes, and distribution of YAP1 protein were investigated in tetraploid embryos produced using the FUTP method. The FUTP method most effectively prevented apoptosis during porcine tetraploid embryo formation. Tetraploid aggregation-derived blastocysts have a high proportion of trophectoderm with increased expression of the CDX2 mRNA and high YAP1 intensity. Highquality blastocysts derived from a tetraploid embryo aggregation can serve as suitable source material for testing the differentiation potential of pluripotent stem cells for blastocyst complementation in pigs.